1997
DOI: 10.1128/jb.179.1.209-216.1997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the Rhizobium meliloti bacA gene: functional interchangeability with the Escherichia coli sbmA gene and phenotypes of mutants

Abstract: The Rhizobium meliloti bacA gene encodes a function that is essential for bacterial differentiation into bacteroids within plant cells in the symbiosis between R. meliloti and alfalfa. An Escherichia coli homolog of BacA, SbmA, is implicated in the uptake of microcin B17, microcin J25 (formerly microcin 25), and bleomycin. When expressed in E. coli with the lacZ promoter, the R. meliloti bacA gene was found to suppress all the known defects of E. coli sbmA mutants, namely, increased resistance to microcin B17,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 50 publications
5
102
1
Order By: Relevance
“…In E. coli, deletion of the bacA isofunctional homolog, sbmA, produces increased resistance to microcins B17 and J25, bleomycin, and Bac7, which is an antimicrobial peptide of mammalian origin (96,113). Similarly, the bacA mutants of S. meliloti and B. abortus show increased resistance to bleomycin relative to the wild type (74,100). Thus, BacA may play a role in the transport of modified peptides across the inner membrane (64).…”
Section: Bacamentioning
confidence: 99%
See 1 more Smart Citation
“…In E. coli, deletion of the bacA isofunctional homolog, sbmA, produces increased resistance to microcins B17 and J25, bleomycin, and Bac7, which is an antimicrobial peptide of mammalian origin (96,113). Similarly, the bacA mutants of S. meliloti and B. abortus show increased resistance to bleomycin relative to the wild type (74,100). Thus, BacA may play a role in the transport of modified peptides across the inner membrane (64).…”
Section: Bacamentioning
confidence: 99%
“…Generally, the loss of bacA function has been associated with an increased resistance to certain antimicrobial peptides (74,96,113). In E. coli, deletion of the bacA isofunctional homolog, sbmA, produces increased resistance to microcins B17 and J25, bleomycin, and Bac7, which is an antimicrobial peptide of mammalian origin (96,113).…”
Section: Bacamentioning
confidence: 99%
“…BacA is required for intracellular infections during Sinorhizobium meliloti plant symbiosis and Brucella abortus animal pathogenesis (64). BacA is also necessary for differentiation of Sinorhizobium meliloti into nitrogen-fixing differentiated cells (bacteroids) (109). Only when active promoters are inserted in the promoter trap will the bacA gene be expressed, resulting in the differentiation process.…”
Section: Selection Strategies In Ivetmentioning
confidence: 99%
“…For example, it seemed unlikely that a reduction in the lipid A VLCFA content could account for the low-level bleomycin resistance phenotype of the S. meliloti bacA-null mutant, since deletion of the bacA homolog, sbmA, in Escherichia coli also gives rise to a similar phenotype (10), despite the fact that the lipid A of E. coli lacks VLCFA modifications (15). Thus, these data suggested that BacA might have additional effects on S. meliloti, resulting in increased sensitization of wild-type S. meliloti toward bleomycin relative to the S. meliloti bacA mutant.…”
mentioning
confidence: 99%
“…Although the precise function of BacA is unknown, S. meliloti and B. abortus bacAnull mutants display a range of phenotypes during growth in complex medium, including low-level resistance to bleomycin, a glycopeptide antibiotic, and increased sensitivity to detergents compared with their respective parent strains (7,10). The detergent sensitivity phenotype led to the discovery that BacA affects the unusual very-long-chain fatty acid (VLCFA) modifications, 27-OHC28:0, 27-OH(␤OMeC4:0)C28, and 29-OHC30:0, of the lipid A in both S. meliloti and B. abortus (5,7).…”
mentioning
confidence: 99%